2017
DOI: 10.1073/pnas.1610417114
|View full text |Cite
|
Sign up to set email alerts
|

Viral and cellular mRNA-specific activators harness PABP and eIF4G to promote translation initiation downstream of cap binding

Abstract: Regulation of mRNA translation is a major control point for gene expression and is critical for life. Of central importance is the complex between cap-bound eukaryotic initiation factor 4E (eIF4E), eIF4G, and poly(A) tail-binding protein (PABP) that circularizes mRNAs, promoting translation and stability. This complex is often targeted to regulate overall translation rates, and also by mRNA-specific translational repressors. However, the mechanisms of mRNA-specific translational activation by RNA-binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 41 publications
4
44
0
Order By: Relevance
“…These include an eIF4G-binding protein encoded by HSV-1 (ICP6) that stimulates eIF4E binding to eIF4G, promotes eIF4E phosphorylation, and stimulates viral mRNA translation (Walsh and Mohr 2006). To capitalize on limiting cytoplasmic PABP availability in HSV-1-infected cells, the viral ICP27 RNA-binding protein may stimulate initiation downstream of cap binding by harnessing PABP and eIF4G in a mechanism similar to that used by the cellular regulator Dazl (Deleted in azoospermia-like) (Smith et al 2017). HCMV increases the overall abundance of eIFs and PABP.…”
Section: Strategies and Mechanisms Used By Viruses That Produce M 7 Gmentioning
confidence: 99%
“…These include an eIF4G-binding protein encoded by HSV-1 (ICP6) that stimulates eIF4E binding to eIF4G, promotes eIF4E phosphorylation, and stimulates viral mRNA translation (Walsh and Mohr 2006). To capitalize on limiting cytoplasmic PABP availability in HSV-1-infected cells, the viral ICP27 RNA-binding protein may stimulate initiation downstream of cap binding by harnessing PABP and eIF4G in a mechanism similar to that used by the cellular regulator Dazl (Deleted in azoospermia-like) (Smith et al 2017). HCMV increases the overall abundance of eIFs and PABP.…”
Section: Strategies and Mechanisms Used By Viruses That Produce M 7 Gmentioning
confidence: 99%
“…Here, we show that EB2 interacts with the cap-binding complexes (CBC in the nucleus and eIF4F in the cytoplasm) and PABP to stabilize the capped structure of the mRNA. Interestingly, the same type of mechanism has recently been proposed for ICP27 (28), suggesting that these two particular viral proteins target the PABP-eIF4G complex to enhance translation initiation from intronless viral mRNAs. Since EB2 is also able to interact with the nuclear cap-binding complex, we can speculate that the nuclear loading of EB2 onto the target mRNA is required in order to facilitate the subsequent recruitment of PABP onto the cytoplasmic eIF4F cap-binding complex.…”
Section: Discussionmentioning
confidence: 61%
“…This suggests that PABP could stabilize the interaction between EB2 and eIF4G. In a recent publication, Smith et al have reported an interaction between ICP27, the EB2 homologous protein from HSV-1, and PABP (28). Moreover, they have shown that although eIF4G and ICP27 do not seem to interact directly, eIF4G associates with ICP27 in the presence of PABP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CSDE1 mainly reprograms cap-independent translation initiation, CSDE1 can also stimulate and repress cap-dependent translation initiation. In capdependent translation processes, eukaryotic translation initiation factor 4G (eIF4G) and poly(A)-binding protein 1 (PABP1) interact with each other to promote the circularization of terminal ribosomes from the 3' end to the 5' end [49][50][51]. Through enhancing the eIF4G-PABP1 interaction, CSDE1 increased the interaction between the 5' cap and poly(A) tail to promote capdependent translation.…”
Section: Promoting and Repressing Cap-dependent Translation Initiationmentioning
confidence: 99%